Current state of the art MRI for the longitudinal assessment of cystic fibrosis. Issue 5 (17th December 2019) - Woods, Jason C.; Wild, Jim M.; Wielpütz, Mark O.; Clancy, John P.; Hatabu, Hiroto; Kauczor, Hans‐Ulrich; van Beek, Edwin J.R.; Altes, Talissa A.
Abstract : Pulmonary MRI can now provide high‐resolution images that are sensitive to early disease and specific to inflammation in cystic fibrosis (CF) lung disease. With specificity and function limited via computed tomography (CT), there are significant advantages to MRI. Many of the modern MRI techniques can be performed throughout life, and can be employed to understand changes over time, in addition to quantification of treatment response. Proton density and T1 /T2 contrast images can be obtained within a single breath‐hold, providing depiction of structural abnormalities and active inflammation. Modern radial and/or spiral ultrashort echo‐time (UTE) techniques rival CT in resolution for depiction and quantification of structure, for both airway and parenchymal abnormalities. Contrast perfusion MRI techniques are now utilized routinely to visualize changes in pulmonary and bronchial circulation that routinely occur in CF lung disease, and noncontrast techniques are moving closer to clinical translation. Functional information can be obtained from noncontrast proton images alone, using techniques such as Fourier decomposition. Hyperpolarized‐gas MRI, increasingly using 129 Xe, is now becoming more widespread and has been demonstrated to have high sensitivity to early airway obstruction in CF via ventilation MRI. The sensitivity of 129 Xe MRI promises future use in personalized medicine, management of early CF lung disease, and in future clinical trials. By combining structural and functional techniques, with or without hyperpolarized gases, regional structure–function relationships can be obtained, giving insight into the pathophysiology of disease and improved clinical management. This article reviews the modern MRI techniques that can routinely be employed for CF lung disease in nearly any large medical center. Level of Evidence: 4 Technical Efficacy Stage: 5 J. Magn. Reson. Imaging 2019.